Polyamide, method for producing the same, and film containing the polyamide
Patent Information
- Application Number
- JP2024128783
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-05-15
- Filing Date
- 2024-08-05
- Publication Date
- 2025-03-26
Smart Images

Figure 2025041528000001 
Figure 2025041528000002 
Figure 2025041528000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyamide and a film having excellent heat resistance, moldability, flexibility and appearance. [Background technology]
[0002] Highly flexible polyamides are widely used in tubes and hoses, everyday shoes, sealing materials, etc. Such polyamides usually contain polyether and / or polyester components to impart flexibility. In recent years, applications of such polyamides in fields such as automobile parts, peripheral parts for electronic devices, and battery materials have been considered, and polyamides used in the above fields are required to have even higher heat resistance.
[0003] To obtain a polyamide with high heat resistance, it is necessary to increase the polymerization temperature, which leads to a problem that the polyether and polyester components used to impart flexibility are decomposed, resulting in a decrease in molecular weight and insufficient performance.
[0004] As a polyamide that does not use a polyether component or a polyester component, Patent Document 1 discloses a polyamide made of adipic acid, 1,4-butylene diamine, dimer acid, and dimer diamine.
[0005] However, although the polyamide described in Patent Document 1 has improved heat resistance, it has a problem in that its flexibility is not sufficiently improved.
[0006] Patent Documents 2 and 3 disclose polyamides having excellent heat resistance and flexibility. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 2014-506614 [Patent Document 2] International Publication No. 2020 / 085360 Brochure [Patent Document 3] International Publication No. 2022 / 054944 Brochure Summary of the Invention [Problem to be solved by the invention]
[0008] However, the polyamide described in Patent Document 2 is polymerized by adding an aliphatic dicarboxylic acid having 18 to 44 carbon atoms, an aliphatic diamine having 18 to 44 carbon atoms, and an aliphatic diamine having 4 to 12 carbon atoms to the aromatic dicarboxylic acid having 4 to 12 carbon atoms as raw materials at almost the same time. Therefore, the aromatic dicarboxylic acid having a high specific gravity may precipitate and become unevenly distributed during the charging stage, and the molecular weight may not be sufficiently increased, or unreacted monomers or salts may remain, resulting in poor appearance.
[0009] On the other hand, the polyamide described in Patent Document 3 is produced by first reacting an aromatic dicarboxylic acid having 4 to 12 carbon atoms, which forms the hard segment, with an aliphatic diamine having 4 to 12 carbon atoms to produce a prepolymer (salt), and then polymerizing it by adding an aliphatic dicarboxylic acid having 18 to 44 carbon atoms and an aliphatic diamine having 18 to 44 carbon atoms, which form the soft segment, in a certain ratio. With this method, a polyamide with high blocking properties is obtained, and heat resistance and flexibility are good, but since the soft segment is long, it tends to flow when melted, which may result in poor moldability, or unreacted monomers or salts may remain, resulting in poor appearance.
[0010] Furthermore, in the conventional techniques, there were cases where the molecular weight was non-uniform, or where the reaction rate of the raw material monomer was insufficient, making it impossible to obtain a high molecular weight.
[0011] The present invention has been made to solve the above problems, and an object of the present invention is to provide a polyamide having excellent heat resistance, moldability, flexibility and appearance, a method for producing the same, and a film containing the polyamide.
[0012] Another object of the present invention is to provide a polyamide excellent not only in heat resistance, moldability, flexibility, and appearance, but also in molecular weight uniformity and high molecular weight properties, a method for producing the same, and a film containing the polyamide. [Means for solving the problem]
[0013] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above object can be achieved by polymerizing polyamide by a specific production method, thereby completing the present invention.
[0014] The gist of the present invention is as follows. <1> A unit consisting of an aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms; Units consisting of an aliphatic diamine (B) having 18 to 48 carbon atoms and / or units consisting of an aliphatic diamine (D) having 4 to 16 carbon atoms; and Units consisting of aromatic / aliphatic dicarboxylic acids (C) with 4 to 12 carbon atoms A polyamide comprising: The polyamide has a melt viscosity of 40 to 200 Pa·s. <2> the content of units composed of the aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms is 30 to 80 mass%, the content of units composed of the aliphatic diamine (B) having 18 to 48 carbon atoms is 0 to 45 mass%, the content of units composed of the aromatic / aliphatic dicarboxylic acid (C) having 4 to 12 carbon atoms is 5 to 25 mass%, and the content of units composed of the aliphatic diamine (D) having 4 to 16 carbon atoms is 10 to 40 mass%, based on all monomer components constituting the polyamide; <1> The polyamide according to claim 1. <3> The aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms is a dimer acid. <1> or <2> The polyamide according to claim 1. <4> The aliphatic diamine (B) having 18 to 48 carbon atoms is a dimer diamine. <1> ~ <3> 2. The polyamide according to claim 1 , <5> The aromatic / aliphatic dicarboxylic acid (C) having 4 to 12 carbon atoms is terephthalic acid. <1> ~ <4> 2. The polyamide according to claim 1 , <6> The aliphatic diamine (D) having 4 to 16 carbon atoms is 1,10-decanediamine. <1> ~ <5> 2. The polyamide according to claim 1 , <7> The polyamide has a melting point of 290° C. or more. <1> ~ <6> 2. The polyamide according to claim 1 , <8> The polyamide has a flexural modulus of 600 MPa or less. <1> ~ <7> 2. The polyamide according to claim 1 , <9> The polyamide has a haze of 60% or less. <1> ~ <8> 2. The polyamide according to claim 1 , <10> The content of the plasticizer component is 0.5% by mass or less based on the polyamide. <1> ~ <9> 2. The polyamide according to claim 1 , <11> a ratio (mass ratio) of a total content of the aromatic / aliphatic dicarboxylic acid (C) and the aliphatic diamine (D) to a total content of the aliphatic dicarboxylic acid (A), the aliphatic diamine (B), the aromatic / aliphatic dicarboxylic acid (C), and the aliphatic diamine (D) is 0.10 to 0.60. <1> ~ <10> 2. The polyamide according to claim 1 , <12> The value of the following formula (1) is 0.30 or less. <1> ~ <11> 2. The polyamide according to claim 1 , (MnMax-MnMin) / MnMax (1) (MnMax and MnMin respectively indicate the maximum and minimum values of the number average molecular weight.) <13> a first polymerization step of reacting an aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms with an aliphatic diamine (B) having 18 to 48 carbon atoms and / or an aliphatic diamine (D) having 4 to 16 carbon atoms; and After the first polymerization step, an aromatic / aliphatic dicarboxylic acid (C) having 4 to 12 carbon atoms is further added and reacted in a second polymerization step. A method for producing a polyamide, comprising: a ratio (mass ratio) of a total amount of the aromatic / aliphatic dicarboxylic acid (C) and the aliphatic diamine (D) used to a total amount of the aliphatic dicarboxylic acid (A), the aliphatic diamine (B), the aromatic / aliphatic dicarboxylic acid (C), and the aliphatic diamine (D) used is 0.10 to 0.60. <14> After the first polymerization step, the unreacted terminal groups of the aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms are 1 The relationship between the peak integrals of the H-NMR spectra and the amine end groups of the reactants and the starting monomers. 1 The percentage of peak integrals in the H-NMR spectrum is 20% or more. <13> A method for producing the polyamide according to claim 1. <15> <1> ~ <12> 2. Producing a polyamide according to any one of the preceding claims. <13> or <14> A method for producing the polyamide according to claim 1. <16> <1> ~ <12> 2. A film comprising the polyamide according to claim 1 . Effect of the Invention
[0015] According to the present invention, it is possible to provide a polyamide having excellent heat resistance, moldability, flexibility and appearance. The polyamide and film of the present invention are excellent in all properties such as heat resistance, moldability, flexibility and appearance, and can therefore be suitably used as packaging materials and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The polyamide of the present invention contains a specific combination of units selected from units consisting of an aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms (hereinafter sometimes referred to as component (A)), units consisting of an aliphatic diamine (B) having 18 to 48 carbon atoms (hereinafter sometimes referred to as component (B)), units consisting of an aromatic / aliphatic dicarboxylic acid (C) having 4 to 12 carbon atoms (hereinafter sometimes referred to as component (C)), and units consisting of an aliphatic diamine (D) having 4 to 16 carbon atoms (hereinafter sometimes referred to as component (D)). Each of the components (A) to (D) that can constitute the polyamide of the present invention is contained in the polyamide as a monomer component (or monomer residue). Therefore, the "unit consisting of an aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms" may be simply expressed as "an aliphatic dicarboxylic acid (A) monomer having 18 to 48 carbon atoms" or a residue thereof. A "unit consisting of an aliphatic diamine (B) having 18 to 48 carbon atoms" may be simply expressed as an "aliphatic diamine (B) monomer having 18 to 48 carbon atoms" or a residue thereof. A "unit consisting of an aromatic / aliphatic dicarboxylic acid (C) having 4 to 12 carbon atoms" may be simply expressed as an "aromatic / aliphatic dicarboxylic acid (C) monomer having 4 to 12 carbon atoms" or a residue thereof. A "unit consisting of an aliphatic diamine (D) having 4 to 16 carbon atoms" may be simply expressed as an "aliphatic diamine (D) monomer having 4 to 16 carbon atoms" or a residue thereof.
[0017] The polyamide of the present invention is A unit consisting of component (A); Units consisting of component (B) and / or units consisting of component (D); and Units consisting of component (C) Specifically, the polyamide of the present invention contains a unit consisting of component (A); at least one of a unit consisting of component (B) or a unit consisting of component (D); and a unit consisting of component (C). More specifically, with regard to the units consisting of components (B) and (C), the polyamide of the present invention may contain either a unit consisting of component (B) or a unit consisting of component (D), or may contain both units. From the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide or a molded product of the polyamide (e.g., a test piece, a film) (hereinafter referred to as "polyamide, etc.") and improving the molecular weight uniformity and high molecular weight properties, the polyamide of the present invention preferably contains at least a unit consisting of component (D) among the units consisting of component (B) and the units consisting of component (D), and more preferably contains both units.
[0018] In this specification, heat resistance refers to the property of the polyamide having a sufficiently higher melting point. Moldability is a property of a polyamide in which the melt viscosity, as measured by a flow tester, is within a suitable range. Flexibility is the property of polyamide having a sufficiently low flexural modulus. The appearance is characterized by the absence of unreacted monomers or salts remaining in the polyamide and a sufficiently low haze. The molecular weight uniformity is the uniformity of the molecular weight of polyamide, which may increase or decrease depending on the lot, and refers to the property of the molecular weight of polyamide being more uniform. High molecular weight properties refer to polyamides with higher molecular weights. Of these properties, the molecular weight uniformity and high molecular weight properties are not necessarily properties that the polyamide etc. of the present invention must have, but are properties that it is preferable for them to have.
[0019] As the component (A), an aliphatic dicarboxylic acid consisting entirely of hydrocarbons except for carboxyl groups is preferred, and examples thereof include hexadecanedicarboxylic acid (carbon number 18), octadecanedicarboxylic acid (carbon number 20), and dimer acid (carbon number 32 to 48 (particularly 36 to 44)). An aliphatic dicarboxylic acid is an acyclic aliphatic compound having two carboxyl groups in one molecule and not containing any aromatic ring such as a benzene ring or a naphthalene ring. Among them, an aliphatic dicarboxylic acid having 20 or more carbon atoms is preferred, and a dimer acid is more preferred, because it has high flexibility. The dimer acid may be a product of an addition reaction between two molecules selected from unsaturated fatty acids having 18 to 22 carbon atoms, such as oleic acid, linoleic acid, and erucic acid. The two molecules may be the same type of molecule or different types of molecules. The dimer acid may be a dicarboxylic acid having an unsaturated bond, but a dicarboxylic acid that is hydrogenated and all bonds are saturated bonds is preferred, because it is difficult to color. The component (A) may be one of the above alone or two or more of them in combination. In this specification, C36 dimer acid refers to a dimer acid having 36 carbon atoms. The C36 dimer acid may be obtained by addition reaction of two molecules selected from unsaturated fatty acids such as oleic acid and linoleic acid. The C44 dimer acid refers to a dimer acid having 44 carbon atoms. The C44 dimer acid may be obtained by addition reaction of two molecules selected from unsaturated fatty acids such as erucic acid.
[0020] The number of carbon atoms in component (A) is preferably 18 to 48, more preferably 18 to 44, even more preferably 20 to 44, sufficiently preferably 20 to 40, even more preferably 30 to 40, and particularly preferably 34 to 38, from the viewpoints of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide or the like, and improving the molecular weight uniformity and high molecular weight properties.
[0021] The content of component (A) is not particularly limited, and from the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of polyamide and the like, as well as improving the molecular weight uniformity and high molecular weight characteristics, it is preferably 30 to 80 mass%, more preferably 30 to 75 mass%, even more preferably 30 to 70 mass%, sufficiently preferably 35 to 65 mass%, more sufficiently preferably 35 to 60 mass%, and particularly preferably 35 to 55 mass%. The content is the content of the residue of component (A) and is the ratio to the total monomer components constituting the polyamide (or the total amount of their residues). When the polyamide contains two or more kinds of components (A), the total amount of them may be within the above range.
[0022] As the component (B), an aliphatic diamine consisting entirely of hydrocarbons except for amino groups is preferred, for example, 1,18-octadecanediamine (carbon number 18), 1,20-eicosanediamine (carbon number 20), and dimer diamine (carbon number 32 to 48 (particularly 36 to 44)). An aliphatic diamine is an acyclic aliphatic compound having two amino groups in one molecule and not containing any aromatic ring such as a benzene ring or a naphthalene ring. Among them, dimer diamine is preferred. By using dimer diamine, the flexibility of the entire polymer can be effectively improved even with a resin composition containing a relatively small amount of dimer diamine compared to other monomers. Usually, dimer diamine is produced by reacting dimer acid with ammonia, followed by dehydration, nitrification, and reduction. Although the dimer diamine may be a diamine having an unsaturated bond, it is preferable to use a diamine in which all bonds are saturated by hydrogenation, since it is difficult to color. As the component (B), one of the above may be used alone, or two or more may be used in combination. N36 dimer diamine refers to a dimer diamine having a carbon number of 36. N36 dimer diamine may be produced, for example, by reacting C36 dimer acid with ammonia, followed by dehydration, nitrification, and reduction.
[0023] From the viewpoints of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide and the like, as well as improving the molecular weight uniformity and high molecular weight properties, the number of carbon atoms in component (B) is preferably 18 to 48, more preferably 18 to 44, even more preferably 18 to 40, sufficiently preferably 18 to 38, even more preferably 24 to 38, even more preferably 32 to 38, and particularly preferably 34 to 38.
[0024] The content of component (B) is not particularly limited, and from the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of polyamide and the like, as well as improving the molecular weight uniformity and high molecular weight properties, it is preferably 0 to 45% by mass, more preferably 0 to 43% by mass, even more preferably 3 to 40% by mass, and particularly preferably 5 to 38% by mass. The content is the content of the residue of component (B) and is the ratio to the total amount of the monomer components constituting the polyamide (or the total amount of their residues). When the polyamide contains two or more kinds of components (B), the total amount of them may be within the above range. Note that the content of component (B) is 0% by mass means that the polyamide does not contain component (B). Therefore, component (B) is an optional component. In detail, component (B) may or may not be contained in the polyamide, and when it is contained, it may be contained within the above range.
[0025] Component (C) is an aromatic / aliphatic dicarboxylic acid (i.e., aromatic or aliphatic dicarboxylic acid), and more specifically, is one or more dicarboxylic acids selected from the group consisting of aromatic dicarboxylic acids and aliphatic dicarboxylic acids. Aromatic dicarboxylic acids are cyclic aromatic compounds having two carboxyl groups and one or more aromatic rings such as benzene rings and naphthalene rings in one molecule. Aliphatic dicarboxylic acids are acyclic aliphatic compounds having two carboxyl groups and no aromatic rings such as benzene rings and naphthalene rings in one molecule. From the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of polyamides and the like, as well as improving the molecular weight uniformity and high molecular weight properties, it is preferable that aromatic / aliphatic dicarboxylic acids (C) are aromatic dicarboxylic acids.
[0026] Examples of component (C) include aliphatic dicarboxylic acids such as sebacic acid (carbon number 10), azelaic acid (carbon number 9), and adipic acid (carbon number 6), and aromatic dicarboxylic acids such as terephthalic acid (carbon number 8) and isophthalic acid (carbon number 8). Among these, aromatic dicarboxylic acids having 8 or more carbon atoms are preferred, and terephthalic acid is more preferred, since they are more likely to further improve heat resistance and flexibility. As component (C), one of the above may be used alone, or two or more may be used in combination.
[0027] The number of carbon atoms in component (C) is preferably 4 to 12, more preferably 6 to 12, even more preferably 6 to 10, sufficiently preferably 7 to 10, and particularly preferably 8 to 10, from the viewpoints of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide and the like, as well as improving the molecular weight uniformity and high molecular weight properties.
[0028] The content of component (C) is not particularly limited, and from the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of polyamide and the like, as well as improving the molecular weight uniformity and high molecular weight properties, it is preferably 5 to 25 mass%, more preferably 5 to 20 mass%, even more preferably 5 to 18 mass%, sufficiently preferably 8 to 15 mass%, and particularly preferably 8 to 12 mass%. The content is the content of the residue of component (C) and is the ratio to the total amount of the monomer components (or the total amount of their residues) constituting the polyamide. When the polyamide contains two or more kinds of components (C), the total amount of them may be within the above range.
[0029] Component (D) is an aliphatic diamine, which is an acyclic aliphatic compound having two amino groups in one molecule and not containing any aromatic ring such as a benzene ring or a naphthalene ring. Examples of component (D) include 1,14-tetradecanediamine (carbon number 14), 1,13-tridecanediamine (carbon number 13), 1,12-dodecanediamine (carbon number 12), 1,11-undecanediamine (carbon number 11), 1,10-decanediamine (carbon number 10), 1,9-nonanediamine (carbon number 9), 1,8-octanediamine (carbon number 8), 1,7-heptanediamine (carbon number 7), 1,6-hexanediamine (carbon number 6), 1,5-pentanediamine (carbon number 5), and 1,4-butanediamine (carbon number 4). Among these, from the viewpoints of further improving moldability, flexibility, and appearance, as well as improving molecular weight uniformity and high molecular weight properties, diamines having 6 or more carbon atoms are preferred, diamines having 8 or more carbon atoms are preferred, diamines having 10 or more carbon atoms are more preferred, and 1,10-decanediamine is even more preferred. As component (D), one of the above may be used alone, or two or more may be used in combination.
[0030] The number of carbon atoms in component (D) is preferably 4 to 16, more preferably 4 to 14, even more preferably 4 to 12, sufficiently preferably 4 to 10, and particularly preferably 8 to 10, from the viewpoints of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide or the like, as well as improving the molecular weight uniformity and high molecular weight properties.
[0031] The content of component (D) is not particularly limited, and from the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of polyamide and the like, as well as improving the molecular weight uniformity and high molecular weight characteristics, it is preferably 10 to 40 mass%, more preferably 10 to 38 mass%, even more preferably 10 to 36 mass%, sufficiently preferably 10 to 35 mass%, more sufficiently preferably 10 to 30 mass%, and particularly preferably 14 to 30 mass%. The content is the content of the residue of component (D) and is the ratio to the total monomer components constituting the polyamide (or the total amount of their residues). When the polyamide contains two or more kinds of components (D), the total amount of them may be within the above range.
[0032] The ratio (mass ratio) of the total content of components (C) and (D) to the total content of components (A) to (D) is usually 0.10 to 0.60, and from the viewpoints of further improving the heat resistance, moldability, flexibility, and appearance of polyamide and the like, as well as improving the molecular weight uniformity and high molecular weight properties, is preferably 0.15 to 0.55, more preferably 0.15 to 0.50, and even more preferably 0.20 to 0.45.
[0033] The polyamide of the present invention preferably does not contain a plasticizer component. The plasticizer component is an additive that is blended into the polymer for the purpose of reducing the melt viscosity of the polymer and / or improving the flexibility of the polymer. Such a plasticizer component may be any compound that is usually used as a plasticizer for polyamides. Specific examples of the plasticizer component include toluenesulfonic acid alkylamide, benzenesulfonic acid alkylamide, and hydroxybenzoic acid alkyl ester. The present invention does not necessarily prevent the polyamide from containing a plasticizer component.
[0034] The content of the plasticizer component is preferably 5% by mass or less, more preferably 1% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less, from the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide, etc., and improving the molecular weight uniformity and high molecular weight properties. The lower limit of the content range is usually 0% by mass. The content is a value relative to the polyamide, and can be measured as the mass loss rate due to heat treatment at 120°C for 72 hours. The plasticizer component is an additive that exists between polyamide molecules by blending or mixing with the polyamide, and is not a component that constitutes a part of the polyamide by covalent bonding with the polyamide.
[0035] The fact that the polyamide of the present invention does not contain a plasticizer component is one of the preferable reasons for using the polyamide of the present invention for film applications, as described below. In more detail, the polyamide of the present invention has flexibility suitable for films even without a plasticizer, so that it is possible to prevent the exudation of plasticizer components during use in a high-temperature atmosphere or over time. The polyamide of the present invention does not lose its mass due to the volatilization of the plasticizer even when used for a long period of time in a high-temperature atmosphere, and does not lose its flexibility.
[0036] The polyamide of the present invention preferably does not contain a polyether component or a polyester component that is easily decomposed during polymerization. Examples of the polyether component include polyoxyethylene glycol, polyoxypropylene glycol, polyoxytetramethylene glycol, and polyoxyethylene-polyoxypropylene glycol. Examples of the polyester component include polyethylene adipate, polytetramethylene adipate, and polyethylene sebacate. When a polyether component or a polyester component is used, decomposition may occur if the polymerization temperature is high.
[0037] The total content of the polyether component and the polyester component is preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.1% by mass or less, from the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide, etc., and improving the molecular weight uniformity and high molecular weight properties. The lower limit of the total content range is usually 0% by mass. The total content is the content of the residues of the polyether component and the polyester component, and is the ratio to the total monomer components (or the total amount of their residues) constituting the polyamide. The polyether component and the polyester component are components that constitute a part of the polyamide through a covalent bond with the polyamide, and are not simply blended into the polyamide.
[0038] The polyamide of the present invention may contain a terminal blocking agent for adjusting the degree of polymerization, inhibiting decomposition or coloring of the product, etc. Examples of the terminal blocking agent include monocarboxylic acids such as acetic acid, lauric acid, benzoic acid, and stearic acid, and monoamines such as octylamine, cyclohexylamine, aniline, and stearylamine. The terminal blocking agent may be used alone or in combination of two or more of the above. The content of the terminal blocking agent is not particularly limited, but is usually 0 to 10 mol% based on the total molar amount of the dicarboxylic acid and the diamine.
[0039] The polyamide of the present invention may contain additives. Examples of additives include fibrous reinforcing materials such as glass fibers and carbon fibers; fillers such as talc, swellable clay minerals, silica, alumina, glass beads, and graphite; pigments such as titanium oxide and carbon black; antioxidants; antistatic agents; flame retardants; and flame retardant assistants. The additives may be added during polymerization or may be added by melt kneading or the like after polymerization. These additives are additives that are blended into the polyamide.
[0040] The melting point (Mp) of the polyamide is usually 200° C. or higher, and from the viewpoint of further improving heat resistance, it is preferably 260° C. or higher, more preferably 290° C. or higher, even more preferably 300° C. or higher, and most preferably 310° C. or higher. The upper limit of the melting point is not particularly limited, and for example, the melting point may usually be 400° C. or lower, particularly 380° C. or lower.
[0041] In this specification, the melting point of a polyamide is determined based on the endothermic peak when the temperature is increased at a rate of 20° C. / min using a differential scanning calorimeter.
[0042] The polyamide of the present invention has excellent moldability, and the melt viscosity of the polyamide measured by a flow tester, which is an index of moldability, must be 40 to 200 Pa·s, preferably 60 to 160 Pa·s, and more preferably 80 to 120 Pa·s. If the melt viscosity is less than 40 Pa·s, it is difficult to form a film and moldability is poor, which is not preferable. On the other hand, if the melt viscosity exceeds 200 Pa·s, it is difficult to extrude and moldability is poor, which is not preferable.
[0043] In this specification, the melt viscosity is measured at a temperature of the melting point of the polyamide + 10°C according to the method described in JIS K 7210-1, and is expressed as a shear viscosity of 1000 s ―1 The value used is:
[0044] The polyamide of the present invention has excellent flexibility, and the flexural modulus of the polyamide, which is an index of flexibility, is preferably 600 MPa or less, and from the viewpoint of further improving flexibility, is more preferably 550 MPa or less, and even more preferably 500 MPa or less.
[0045] In this specification, the flexural modulus is a value measured at 23° C. in accordance with ISO178 using a test piece having dimensions of 120 mm×10 mm×4 mm and made only of polyamide.
[0046] The polyamide of the present invention has no particulate matter in the chips, low film haze, and excellent appearance. The haze of the polyamide, which is an indicator of the appearance of the film, is preferably 60% or less, more preferably 40% or less, and even more preferably 30% or less.
[0047] In this specification, the haze of a polyamide is a value measured by using a film of the polyamide under the following measurement conditions according to the method described in JIS K 7136. Measurement conditions: -Haze meter (Nippon Denshoku Industries Co., Ltd. NDH4000) ·Temperature 23℃ Light source: Halogen lamp (5V, 9W). Thickness: 100μm
[0048] The polyamide films used to measure the haze are 100 μm-thick stretched films obtained by simultaneously biaxially stretching an unstretched film containing only 100 parts by mass of polyamide pellets and 0.4 parts by mass of Sumilizer GA-80 under the following conditions, except for Comparative Examples 1 to 5. The polyamide films used to measure the haze are 100 μm-thick pressed films obtained by pressing the polyamide pellets at melting point +10° C. using a hydraulic press. Stretching conditions: MD stretch ratio: 2.3 times TD stretch ratio is 2.3 times.
[0049] The polyamide of the present invention is preferably excellent in molecular weight uniformity, and the value of the variation in the following formula (1), which is an index of molecular weight uniformity, is preferably 0.40 or less, more preferably 0.30 or less, even more preferably 0.20 or less, and most preferably 0.10 or less. The lower limit of the variation is not particularly limited, and the variation may be, for example, 0.001 or more, particularly 0.01 or more. (MnMax-MnMin) / MnMax (1)
[0050] In this specification, MnMax in the above formula (1) is the largest number average molecular weight (maximum value) among lots polymerized five or more times to have the same resin composition, and MnMin is the smallest number average molecular weight (minimum value). The number average molecular weight Mn is expressed by 1 The number average molecular weight Mn determined from the amount of terminal groups by H-NMR analysis is used.
[0051] The polyamide of the present invention preferably has excellent high molecular weight characteristics, and the average value of the number average molecular weight Mn is preferably 10000 or more, more preferably 15000 or more, even more preferably 20000 or more, sufficiently preferably 30000 or more, and even more preferably 40000 or more. The upper limit of the average value of the number average molecular weight is not particularly limited, and the average value of the number average molecular weight may be, for example, 100000 or less, preferably 80000 or less, and particularly 50000 or less.
[0052] In this specification, the average value of the number average molecular weight Mn is 1 The number average molecular weight Mn determined from the amount of terminal groups by H-NMR analysis is the average value of five lots.
[0053] The polyamide of the present invention can be produced by a two-stage polymerization method. Specifically, the polyamide of the present invention can be produced by a method including a first polymerization step in which component (A) is reacted with component (B) and / or component (D), and a second polymerization step in which component (C) is further added and reacted after the first polymerization step. More specifically, in a preferred method for producing the polyamide of the present invention, at least one acid component and one amine component are selected from components (A), (B), and (D), and are sufficiently reacted at a polymerization temperature at which they are unlikely to volatilize to increase the viscosity (first polymerization step), and then component (C) is further added and is sufficiently reacted (second polymerization step). In the first polymerization step, when component (C) (e.g., terephthalic acid) is added, the component (C) precipitates due to its relatively high specific gravity and cannot be dispersed well in the system and segregates, so that the molecular weight cannot be sufficiently increased, or unreacted monomers and salts remain, resulting in poor appearance. In the first polymerization step, whether component (C) is added all at once or in portions, the molecular weight may not be sufficiently increased, or unreacted monomers or salts may remain, resulting in poor appearance.
[0054] In the first polymerization step, generally, all of the monomer components constituting the polyamide to be produced, except for component (C), are used. For example, when producing a polyamide containing components (A) to (D) as monomer components, components (A), (B) and (D) are used in the first polymerization step. As a specific example, when producing a polyamide containing dimer acid, dimer diamine, terephthalic acid and 1,10-decanediamine as monomer components as components (A) to (D), respectively, dimer acid is used as component (A), and dimer diamine and 1,10-decanediamine are used as components (B) and (D), respectively, in the first polymerization step. Also, for example, when producing a polyamide containing components (A), (C) and (D) as monomer components, components (A) and (D) are used in the first polymerization step. As a specific example, when producing a polyamide containing dimer acid as component (A), terephthalic acid as component (C), and 1,10-decanediamine as component (D), respectively, as monomer components, dimer acid is used as component (A) and 1,10-decanediamine is used as component (D) in the first polymerization step. If component (C) is used in the first polymerization step, the component (C) used in the first polymerization step remains, even if component (C) is used in the subsequent second polymerization step, and the appearance is deteriorated.
[0055] In the first polymerization step, since the diamine component is used in an excess amount, an amino-terminated prepolymer is usually synthesized. Therefore, the above-mentioned two-stage polymerization method as the method for producing the polyamide of the present invention can also be called an "amino-terminated prepolymer synthesis type two-stage polymerization method". Even if the production method is classified as the same two-stage polymerization method, in the "salt synthesis type two-stage polymerization method" as described in Patent Document 3, an aromatic dicarboxylic acid having 4 to 12 carbon atoms and an aliphatic diamine having 4 to 12 carbon atoms, which form the hard segment, are usually reacted first to generate a prepolymer (salt), and then an aliphatic dicarboxylic acid having 18 to 44 carbon atoms and an aliphatic diamine having 18 to 44 carbon atoms, which form the soft segment, are added in a certain ratio and polymerized. In this method, a polyamide with high block properties is obtained and has good heat resistance and flexibility, but since the soft segment is long, it is easy to flow when melted, and the melt viscosity is difficult to increase, and poor appearance occurs.
[0056] The polymerization temperature (reaction temperature) in the first polymerization step is preferably 100 to 190°C, more preferably 130 to 180°C, and even more preferably 160 to 180°C. If the polymerization temperature is below 100°C, the polymerization reaction does not proceed. On the other hand, if the polymerization temperature exceeds 190°C, component (D) (e.g., 1,10-decanediamine) volatilizes, the molar balance is lost, and molecular weight control becomes difficult. More specifically, a sufficiently high molecular weight cannot be achieved.
[0057] By providing the first polymerization step in this way, the melt viscosity of the reaction product (or oligomer or prepolymer) of components (A), (B) and / or (D) increases before the addition of component (C). Therefore, even if component (C) with a relatively high specific gravity is added in the subsequent second polymerization step, segregation due to precipitation is unlikely to occur, the reaction proceeds more uniformly, and the molecular weight can be increased, resulting in a good appearance. Component (C) may be added in portions or all at once.
[0058] In the first polymerization step, the polymerization time is not particularly limited, and may be, for example, 0.5 to 5 hours, preferably 3 to 5 hours, and particularly 1 to 3 hours. From the viewpoint of molecular weight uniformity and high molecular weight characteristics, the polymerization time in the first polymerization step is preferably a time such that the reaction rate of the raw material monomer after the first polymerization step is 20% or more, and from the viewpoint of the reaction rate, it is preferably 3 to 5 hours. From the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of polyamide and the like, and improving molecular weight uniformity and high molecular weight characteristics, the reaction rate of the raw material monomer after the first polymerization step is preferably 20% or more, more preferably 40% or more, even more preferably 50% or more, sufficiently preferably 60% or more, and more sufficiently preferably 80% or more. Note that the reaction rate of the raw material monomer after the first polymerization step is determined by the ratio of the terminal groups of the aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms before the first polymerization step to the total terminal groups of the aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms before the first polymerization step. 1 The relationship between the peak integral value of the H-NMR spectrum and the amine end group in the reaction system after the first polymerization step. 1 It is the percentage of the total peak integral value of the H-NMR spectrum.
[0059] The polymerization temperature (reaction temperature) in the second polymerization step is usually 230 to 340°C, preferably 240 to 320°C, more preferably 250 to 300°C, and even more preferably 260 to 290°C. In the second polymerization step, from the viewpoint of increasing the molecular weight and further improving the heat resistance, moldability, flexibility, and appearance of polyamide, etc., and improving the molecular weight uniformity and high molecular weight characteristics, it is preferable to carry out a polymerization reaction at a relatively low temperature within the above polymerization temperature range, and then a polymerization reaction at a relatively high temperature. In the second polymerization step, from the viewpoint of increasing the molecular weight and further improving the heat resistance, moldability, flexibility, and appearance of polyamide, etc., and improving the molecular weight uniformity and high molecular weight characteristics, it is preferable to carry out a polymerization reaction at a relatively low temperature within the above polymerization temperature range, and then a polymerization reaction at a relatively medium temperature and a relatively high temperature in sequence. Such a low temperature is, for example, preferably 230 to 250°C, more preferably 235 to 245°C. The intermediate temperature means a temperature between low and high temperatures, and is, for example, preferably 250 to 270°C, more preferably 255 to 265°C. The high temperature is, for example, preferably 280 to 300°C, more preferably 285 to 295°C. In this case, it is preferable that the addition of component (C) is completed by the time of the polymerization reaction stage at intermediate temperature. For example, it is preferable that the addition of component (C) is completed at the polymerization reaction stage at low temperature.
[0060] In the second polymerization step, the polymerization time is not particularly limited, and may be, for example, 0.5 to 5 hours, particularly 1 to 3 hours in total, in any case where the second polymerization step is carried out in one stage, in two stages at low temperature and high temperature, or in three stages at low temperature, medium temperature, and high temperature. In particular, when the second polymerization step is carried out in three stages at low temperature, medium temperature, and high temperature, each stage may be independently, for example, 0.1 to 3 hours, particularly 0.5 to 2 hours.
[0061] In the first and second polymerization steps, the amounts of the components (A) to (D) used may be any amounts that achieve the contents of the components (A) to (D) in the polymer composition described above. For the amount of each of the components (A) to (D) used, in detail, the ratio (molar ratio) of "total of diamine components / total of dicarboxylic acid components" is preferably 0.95 to 1.15, and from the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide and the like, as well as improving the molecular weight uniformity and high molecular weight properties, it is more preferably 0.97 to 1.10, even more preferably 1.00 to 1.06, sufficiently preferably 1.00 to 1.04, and particularly preferably 1.01 to 1.03. Here, the ratio of "total of diamine components / total of dicarboxylic acid components" refers to the ratio regarding the amounts of components (A) to (D) used, and more specifically, it is the molar ratio of the total amount of components (B) and (D) (diamine components) to the total amount of components (A) and (C) (dicarboxylic acid components).
[0062] Regarding the amounts of the components (A) to (D), more specifically, the ratio (mass ratio) of the total amount of the components (C) and (D) to the total amount of the components (A) to (D) is usually 0.10 to 0.60, and from the viewpoints of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide, etc., and improving the molecular weight uniformity and high molecular weight properties, it is preferably 0.15 to 0.55, more preferably 0.15 to 0.50, and even more preferably 0.20 to 0.45. If the ratio of the total amount of the components (C) and (D) is too high, the moldability, flexibility, and appearance of the polyamide, etc. are reduced.
[0063] The polyamide of the present invention can be suitably used particularly as a film.
[0064] The film of the present invention may contain the polyamide of the present invention described above, and may further contain other polymers. The content of the polyamide of the present invention in the film is usually 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, based on the total amount of the film.
[0065] The film of the present invention can be produced as an unstretched film by melt mixing at Mp+5 to Mp+30 (°C) (for example, 240 to 340°C) for 3 to 15 minutes, extruding the extrudate into a sheet through a T-die, and cooling the extrudate by contacting it with a drum whose temperature is adjusted to -10 to 80°C. The unstretched film can be further stretched. The unstretched film obtained can be used in an unstretched state, but is usually used as a stretched film. The stretching is preferably performed in a uniaxial or biaxial direction, and more preferably in a biaxial direction. Examples of the stretching method include a simultaneous stretching method and a sequential stretching method. Mp is the melting point (°C) of the polyamide described above.
[0066] An example of the simultaneous biaxial stretching method is a method in which an unstretched film is simultaneously biaxially stretched, followed by heat setting. Stretching is preferably performed at 30 to 150°C at 1.5 to 5 times in both the transverse direction (hereinafter sometimes abbreviated as "TD") and the longitudinal direction (hereinafter sometimes abbreviated as "MD"). Heat setting is preferably performed at 150 to 300°C for several seconds with a relaxation treatment in TD at a few percent. Prior to simultaneous biaxial stretching, the film may be subjected to preliminary longitudinal stretching at about 1 to 1.2 times.
[0067] An example of the sequential biaxial stretching method is a method in which an unstretched film is subjected to a heat treatment such as roll heating or infrared heating, stretched in the longitudinal direction, and then continuously stretched in the transverse direction and heat set. The longitudinal stretching is preferably performed at 30 to 150°C and 1.5 to 5 times. The transverse stretching is preferably performed at 30 to 150°C, the same as the longitudinal stretching. The transverse stretching is preferably performed at 1.5 times or more. The heat set treatment is preferably performed at 150 to 300°C for several seconds with a TD relaxation of several percent.
[0068] In the film manufacturing apparatus, the surfaces of the cylinder, the melting part of the barrel, the measuring part, the single tube, the filter, the T-die, etc. are preferably subjected to a treatment to reduce the roughness of the surface in order to prevent the resin from staying. For example, a method of reducing the roughness of the surface may be a method of modifying the surface with a substance having low polarity. Alternatively, a method of depositing silicon nitride or diamond-like carbon on the surface may be used.
[0069] Examples of methods for stretching the film include flat-type sequential biaxial stretching, flat-type simultaneous biaxial stretching, and tubular stretching. Among these, it is preferable to employ flat-type simultaneous biaxial stretching from the viewpoint of improving the thickness accuracy of the film and making the MD properties of the film uniform.
[0070] Examples of the stretching device for employing the flat-type simultaneous biaxial stretching method include a screw-type tenter, a pantograph-type tenter, and a linear motor-driven clip-type tenter.
[0071] Examples of the heat treatment method after stretching include known methods such as a method of blowing hot air, a method of irradiating infrared rays, a method of irradiating microwaves, etc. Among these, the method of blowing hot air is preferred because it allows uniform and accurate heating.
[0072] The film of the present invention may contain an impact-resistant agent in order to further improve flexibility and elongation. Examples of the impact-resistant agent include thermoplastic elastomers such as polyolefin-based thermoplastic elastomers, polyester-based elastomers, polyamide-based elastomers, and styrene-based elastomers. The thermoplastic elastomer preferably has a functional group capable of reacting with an amino group or a carboxyl group, which is a terminal group, and an amide group in the main chain. Examples of the functional group include a carboxyl group or an anhydride thereof, an amino group, a hydroxyl group, an epoxy group, an amide group, and an isocyanate group, and among these, a carboxyl group or an anhydride thereof is preferred. From the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide film, as well as improving the molecular weight uniformity and high molecular weight properties, the impact-resistant agent is preferably a polyolefin-based thermoplastic elastomer (e.g., unmodified polyolefin, acid-modified polyolefin), and more preferably an acid-modified polyolefin (particularly maleic anhydride-modified polyolefin). Specific examples of the impact-resistant agent include, for example, Tafmer MH7020 (manufactured by Mitsui Chemicals, Inc., maleic anhydride-modified polyolefin), Tafmer MH8510 (manufactured by Mitsui Chemicals, Inc., maleic anhydride-modified polyolefin), Tafmac M1913 (manufactured by Asahi Kasei Corporation, maleic anhydride-modified polystyrene-hydrogenated polybutadiene copolymer), and Tafmer A1050S (manufactured by Mitsui Chemicals, Inc., acid-unmodified polyolefin). The impact-resistant agent may be added at any stage in the production of the film. For example, the impact-resistant agent may be added during or before melt mixing of polyamide in the production of the unstretched film. Also, for example, the impact-resistant agent may have the form of pellets that are melt-mixed with polyamide in advance prior to the production of the unstretched film.
[0073] The content of the impact-resistant agent is not particularly limited, and from the viewpoint of further improving the heat resistance, moldability, flexibility, and appearance of the polyamide film as well as improving the molecular weight uniformity and high molecular weight characteristics, it is preferably 30 parts by mass or less (i.e., 0 to 20 parts by mass), more preferably 0 to 20 parts by mass, even more preferably 2 to 20 parts by mass, and particularly preferably 5 to 15 parts by mass, per 100 parts by mass of polyamide.
[0074] It is preferable that the film of the present invention contains a heat stabilizer in order to increase the heat stability during film formation, prevent deterioration of the strength and elongation of the film, and prevent deterioration of the film during use due to oxidation, decomposition, etc. Examples of the heat stabilizer include hindered phenol-based heat stabilizers, hindered amine-based heat stabilizers, phosphorus-based heat stabilizers, sulfur-based heat stabilizers, and bifunctional heat stabilizers.
[0075] Examples of the hindered phenol-based heat stabilizer include Irganox1010 (registered trademark) (manufactured by BASF Japan, pentaerythritol tetrakis [3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]), Irganox1076 (registered trademark) (manufactured by BASF Japan, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), and Cyanox1790 (registered trademark) (manufactured by Solvay, 1,3,5-tris(4-t-butyl-3-hydroxy-2,6 -dimethylbenzyl)isocyanuric acid), Irganox1098 (registered trademark) (manufactured by BASF Japan, N,N'-(hexane-1,6-diyl)bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide]), and Sumilizer GA-80 (registered trademark) (manufactured by Sumitomo Chemical Co., Ltd., 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane).
[0076] An example of the hindered amine-based heat stabilizer is Nylostab S-EED (registered trademark) (manufactured by Clariant Japan, N,N'-bis-2,2,6,6-tetramethyl-4-piperidinyl-1,3-benzenedicarboxamide).
[0077] Examples of phosphorus-based heat stabilizers include Irgafos168 (registered trademark) (manufactured by BASF Japan, tris(2,4-di-tert-butylphenyl)phosphite), Irgafos12 (registered trademark) (manufactured by BASF Japan, 6,6',6"-[nitrilotris(ethyleneoxy)]tris(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepine)), Irgafos38 (registered trademark) (manufactured by BASF Japan, bis(2,4-di-tert-butyl-6-methylphenyl)ethyl phosphite), ADKSTAB329K (registered trademark) (manufactured by ADEKA, tris(mono-dinonylphenyl)phosphite), ADKSTAB PEP36 (registered trademark) (manufactured by ADEKA, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite), and Hostanox Examples of such products include P-EPQ (registered trademark) (manufactured by Clariant, tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenyl diphosphonite), GSY-P101 (registered trademark) (manufactured by Sakai Chemical Industry Co., Ltd., tetrakis(2,4-di-tert-butyl-5-methylphenyl)-4,4'-biphenylene diphosphonite), and Sumilizer GP (registered trademark) (manufactured by Sumitomo Chemical Co., Ltd., 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]-dioxaphosphepine).
[0078] Examples of sulfur-based heat stabilizers include DSTP "YOSHITOMI" (registered trademark) (manufactured by Mitsubishi Chemical Corporation, chemical formula name: distearyl thiodipropionate) and Seenox 412S (registered trademark) (manufactured by Shipro Chemical Co., Ltd., pentaerythritol tetrakis-(3-dodecylthiopropionate)).
[0079] Examples of bifunctional heat stabilizers include Sumilizer GM (registered trademark) (manufactured by Sumitomo Chemical Co., Ltd., 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate) and Sumilizer GS (registered trademark) (manufactured by Sumitomo Chemical Co., Ltd., 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate).
[0080] From the viewpoint of preventing deterioration of film strength, hindered phenol-based heat stabilizers are preferred. The thermal decomposition temperature of the hindered phenol-based heat stabilizer is preferably 320°C or higher, more preferably 350°C or higher. An example of a hindered phenol-based heat stabilizer having a thermal decomposition temperature of 320°C or higher is Sumilizer GA-80. In addition, if the hindered phenol-based heat stabilizer has an amide bond, it can prevent deterioration of film strength. For example, an example of a hindered phenol-based heat stabilizer having an amide bond is Irganox 1098. In addition, by using a bifunctional heat stabilizer in combination with the hindered phenol-based heat stabilizer, deterioration of film strength can be further reduced.
[0081] These heat stabilizers may be used alone or in combination of two or more. For example, by using a hindered phenol-based heat stabilizer and a phosphorus-based heat stabilizer in combination, it is possible to prevent the pressure rise of the raw material filtration filter during film formation and to prevent the deterioration of the film strength. In addition, by using a hindered phenol-based heat stabilizer, a phosphorus-based heat stabilizer, and a bifunctional heat stabilizer in combination, it is possible to prevent the pressure rise of the raw material filtration filter during film formation and to further reduce the deterioration of the film strength.
[0082] A preferred combination of a hindered phenol-based heat stabilizer and a phosphorus-based heat stabilizer is a combination of Sumilizer GA-80 or Irganox 1098 and Hostanox P-EPQ or GSY-P101. A preferred combination of a hindered phenol-based heat stabilizer, a phosphorus-based heat stabilizer and a bifunctional heat stabilizer is a combination of Sumilizer GA-80 or Irganox 1098 and Hostanox P-EPQ or GSY-P101 and Sumilizer GS, and a more preferred combination is Sumilizer GA-80, GSY-P101 and Sumilizer GS.
[0083] The content of the heat stabilizer in the film of the present invention is preferably 0.01 to 2 parts by mass, more preferably 0.04 to 1 part by mass, based on 100 parts by mass of polyamide (A). By setting the content of the heat stabilizer to 0.01 to 2 parts by mass, thermal decomposition can be more efficiently suppressed. When two or more types of heat stabilizers are used in combination, it is preferable that each of the individual contents of the heat stabilizers and the total content of the heat stabilizers are both within the above range.
[0084] The film of the present invention may contain lubricant particles to improve the lubrication property. Examples of the lubricant particles include inorganic particles such as silica, alumina, titanium dioxide, calcium carbonate, kaolin, and barium sulfate, and organic fine particles such as acrylic resin particles, melamine resin particles, silicone resin particles, and crosslinked polystyrene particles.
[0085] The film of the present invention may contain various additives as necessary within the range that does not impair the effects of the present invention. Examples of additives include colorants such as pigments and dyes, coloring inhibitors, antioxidants different from the above-mentioned heat stabilizers, weather resistance improvers, flame retardants, plasticizers, release agents, reinforcers, modifiers, antistatic agents, ultraviolet absorbers, antifogging agents, and various polymers. Examples of pigments include titanium oxide, etc. Examples of weather resistance improvers include benzotriazole-based compounds, etc. Examples of flame retardants include bromine-based flame retardants and phosphorus-based flame retardants, etc. Examples of reinforcers include talc, etc. The various additives may be added at any stage during the production of the film.
[0086] If necessary, the film of the present invention may be subjected to a treatment for improving the adhesiveness of its surface, for example, corona treatment, plasma treatment, acid treatment, or flame treatment.
[0087] The surface of the film of the present invention may be coated with various coating agents in order to impart functions such as easy adhesion, antistatic properties, releasability, and gas barrier properties.
[0088] The film of the present invention (particularly the stretched film) may be laminated with inorganic materials such as metals or oxides thereof, other polymers, paper, woven fabric, nonwoven fabric, wood, and the like.
[0089] The film of the present invention has excellent heat resistance, and the melting point of the film, which is an index of heat resistance, is preferably 200° C. or higher, more preferably 290° C. or higher, and even more preferably 310° C. or higher.
[0090] In this specification, the melting point of the polyamide film is a value measured using a differential scanning calorimeter under the conditions described below.
[0091] The obtained film may be cut into sheets, or may be wound around a winding roll to form a film roll. From the viewpoint of productivity in various applications, the film is preferably in the form of a film roll. When the film is in the form of a film roll, it may be slit to a desired width.
[0092] The film obtained as described above is excellent in heat resistance, moldability, flexibility, molecular weight uniformity, high molecular weight properties and appearance.Therefore, the film of the present invention can be used for a wide variety of applications, including: packaging materials for medicines; packaging materials for food such as retort foods; packaging materials for electronic parts such as semiconductor packages; electrical insulating materials for motors, transformers, cables, electric wires, multilayer printed wiring boards, etc.; dielectric materials for capacitors, etc.; magnetic tape materials such as cassette tapes, magnetic tapes for storing data for digital data storage, and video tapes; protective materials for solar cell substrates, liquid crystal panels, conductive films, glass, digital signage, and other display devices; electronic substrate materials such as LED mounting substrates, organic EL substrates, flexible printed wiring boards, flexible flat cables, flexible antennas, and speaker diaphragms; heat-resistant protective films such as coverlay films for flexible printed wiring and heat-resistant masking tapes; heat-resistant adhesive films such as heat-resistant barcode labels and various industrial process tapes; heat-resistant reflectors; heat-resistant release films; thermally conductive films. The film can be suitably used as a film for semiconductor processes such as dicing tape, dicing tape integrated die attachment film (dicing-die attachment film), dicing tape integrated die bonding film (dicing-die bonding film), dicing tape integrated wafer back surface protection film, back gliding film, etc.; molding decoration materials such as in-mold molding, film insert molding, vacuum molding, and compressed air molding; adhesive materials such as interlayer adhesives for laminates and multilayer printed wiring boards, bonding sheets for flexible printed wiring boards, bonding sheets for flexible flat cables, and bonding sheets for coverlay films; shock absorbing materials such as tube coating, wire coating, shock absorbing films, and sealing films; photographic films; agricultural materials; medical materials; civil engineering and building materials; household and industrial materials such as filtration membranes; and films for textile materials. The film of the present invention may be used for the above applications as it is, or may be stretched and used for the above applications as a stretched film. EXAMPLES
[0093] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. A. Evaluation Methodology The physical properties of the polyamide and polyamide film were measured by the following methods.
[0094] (1) Resin composition The pellets, powders, and films obtained were analyzed using a high-resolution nuclear magnetic resonance apparatus (ECA-500NMR manufactured by JEOL Ltd.). 1 The peak intensities of the copolymerization components were determined by H-NMR analysis (resolution: 500 MHz, solvent: a mixed solvent of deuterated trifluoroacetic acid and deuterated chloroform in a volume ratio of 4 / 5, temperature: 23° C.). In Tables 2, 4, and 6, the resin compositions are shown in mass % as the final composition.
[0095] (2) Reaction rate of raw material monomer in the first polymerization step The reaction product obtained in the first polymerization step was analyzed using a high-resolution nuclear magnetic resonance spectrometer (ECA-500NMR manufactured by JEOL Ltd.) to determine the terminal groups of the unreacted aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms. 1 The relationship between the peak integrals of the H-NMR spectra and the amine end groups of the reactants and the starting monomers. 1 The ratio of peak integral values of the H-NMR spectrum was determined (resolution: 500 MHz, solvent: a mixed solvent of deuterated trifluoroacetic acid and deuterated chloroform in a volume ratio of 4 / 5, temperature: 23° C.).
[0096] (3) Melting point (heat resistance) A few milligrams of the pellets or film obtained were taken and heated to 350°C at a heating rate of 20°C / min using a differential scanning calorimeter (PerkinElmer DSC-7 model), then held at 350°C for 5 minutes, cooled to 25°C at a heating rate of 20°C / min, held at 25°C for a further 5 minutes, and then heated again at a heating rate of 20°C / min. ◎: 310℃ or higher (best); ○: 290°C or higher and lower than 310°C (good); △: 200°C or higher and lower than 290°C (no practical problems); ×: Less than 200°C (problems in practical use).
[0097] (4) Melt viscosity (moldability) The obtained pellets were measured by a flow tester (Shimadzu Corporation CFT-500D) under the conditions of a temperature of melting point of the resin (particularly polyamide) + 10°C, preheating for 3 minutes, L / D = 10, and loads of 5 to 100 kg, three points selected according to the method described in JIS K 7210-1. ―1 The value at which this occurs was taken as the melt viscosity. ◎: 80 Pa·s or more and 120 Pa·s or less (best); ○: 60 Pa·s or more but less than 80 Pa·s or more than 120 Pa·s but less than 160 Pa·s (good); △: 40 Pa·s or more but less than 60 Pa·s, or more than 160 Pa·s but less than 200 Pa·s (no practical problems); ×: Less than 40 Pa·s or more than 200 Pa·s, or not measurable.
[0098] (5) Flexural modulus (flexibility) The pellets obtained were thoroughly dried and then molded using an injection molding machine (Japan Steel Works, Ltd., J35AD-30H) under conditions of cylinder temperature Mp-45 to Mp+20 (°C) (e.g., 270 to 335°C) and mold temperature 30 to 45°C to prepare test pieces of 120 mm x 10 mm x 4 mm. The flexural modulus at 23°C was measured using the obtained test pieces in accordance with ISO178. ◎: 500MPa or less (best); ○: More than 500 MPa and less than 550 MPa (good); △: More than 550 MPa and less than 600 MPa (no practical problems); ×: Exceeds 600 MPa (problems in practical use).
[0099] (6) Appearance The appearance of the obtained pellets and film was evaluated. First, it was confirmed whether particulate matter was observed in the obtained pellets. Furthermore, the haze of the obtained film was measured using a haze meter (NDH4000 manufactured by Nippon Denshoku Industries Co., Ltd.) under conditions of a temperature of 23°C and a halogen lamp (5V, 9W) as a light source, according to the method described in JIS K 7136. ◎: No particulate matter was observed and the haze was 30% or less (best); ○: No particulate matter was observed, and the haze was more than 30% and 40% or less (good); △: No particulate matter was observed, and the haze was more than 40% and not more than 60% (no problem in practical use); ×: Granular matter was observed or the haze was more than 60% (problematic for practical use).
[0100] (7) Overall rating Among the evaluation results regarding melting point, melt viscosity, flexural modulus, and appearance, the lowest evaluation result was used as the overall evaluation result.
[0101] (8) Average value of number average molecular weight Mn (high molecular weight characteristic) and variation of number average molecular weight Mn (molecular weight uniformity) The obtained polyamide was analyzed for each lot using a high-resolution nuclear magnetic resonance apparatus (ECA-500NMR manufactured by JEOL Ltd.). 1 The number average molecular weight Mn was determined from the amount of terminal groups by H-NMR analysis. The average value of the five lots was taken as the average number average molecular weight Mn. Furthermore, among the five lots, the largest number average molecular weight (maximum value) was designated as MnMax, and the smallest number average molecular weight (minimum value) was designated as MnMin, and the variation was calculated using the following formula (1). (MnMax-MnMin) / MnMax (1) ◎: 0.10 or less (best); 〇: More than 0.10 and less than 0.20 (good); △: More than 0.20 and 0.40 or less (no problem in practical use); ×: More than 0.30 (problems in practical use).
[0102] B. Monomer raw materials The C36 dimer acid is an aliphatic dicarboxylic acid having 36 carbon atoms per molecule, and Pripol 1009 (manufactured by Cargill), which is a dimer of an unsaturated fatty acid having 18 carbon atoms, was used. The C44 dimer acid is an aliphatic dicarboxylic acid having 44 carbon atoms per molecule, and Pripol 1004 (manufactured by Cargill), which is a dimer of an unsaturated fatty acid having 22 carbon atoms, was used. N36 dimer diamine is an aliphatic diamine having 36 carbon atoms per molecule, and is a diamine derived from a dimer (dimer acid) of an unsaturated fatty acid having 18 carbon atoms; Priamine 1075 (manufactured by Cargill) was used. The polyamide 12 used was manufactured by DAICEL EVONIK (L2121). 1,10-Decanediamine (N10) 1,11-Undecanediamine (N11) 1,4-Butanediamine (N4) 1,6-Hexanediamine (N6)
[0103] Example 1 Polymerization (Method C: Amino-terminated prepolymer synthesis type two-stage polymerization method, component (C) added all at once) A reaction vessel equipped with a heating mechanism, a stirring mechanism, a nitrogen gas inlet, a condensation water outlet, a pressure release port, and a raw material inlet was charged with 31.72 parts by mass of C36 dimer acid (A), 41.11 parts by mass of N36 dimer diamine (B), 11.92 parts by mass of 1,10-decanediamine (D), and 0.20 parts by mass of sodium hypophosphite monohydrate (aqueous solution adjusted to a solid content concentration of 40% by mass) as a catalyst. After that, nitrogen gas with a purity of 99.9999% was purged from the nitrogen gas inlet to replace the inside of the reaction vessel with nitrogen. First polymerization step: Next, the reaction vessel was heated to 170°C under a nitrogen purged atmosphere while stirring, and heated for about 2 hours. (At this time, the condensed water generated by the polycondensation reaction in the system became water vapor and was discharged outside the system, so the temperature at the condensed water discharge outlet showed 100 to 110°C.) Second polymerization step: After that, the polymerization reaction in the reaction vessel subsided, and the temperature of the condensation water outlet dropped to 90°C, and then the temperature of the reaction vessel was raised to 240°C at a heating rate of 10°C / 10 minutes. Immediately after the temperature inside the reaction vessel reached 240°C, 15.17 parts by mass of (C) terephthalic acid was added all at once from the raw material inlet of the reaction vessel and polymerized for 1 hour. (At this time, the temperature of the condensation water outlet showed 95 to 120°C.) After the temperature of the condensation water outlet dropped to around 90°C, the temperature of the reaction vessel was raised to 260°C at a heating rate of 10°C / 10 minutes, and the reaction was allowed to proceed for 1 hour, and then the temperature was raised to 290°C at a heating rate of 10°C / 10 minutes. Then, polymerization was carried out at 290°C for 1 hour. After the polymerization was completed, the product was discharged in the form of a strand, which was cooled, cut, and dried to obtain polyamide pellets. The above procedure was repeated five times, and the resulting polyamide pellets were mixed in a blender.
[0104] · Film production (simultaneous biaxially stretched film) 100 parts by mass of the obtained pellets and 0.4 parts by mass of Sumilizer GA-80 were dry-blended, and the mixture was put into a twin-screw extruder with a screw diameter of 26 mm and the cylinder temperature was heated to the melting point of the resin (particularly polyamide) + 10°C, melt-kneaded, and extruded into a strand shape. The mixture was then cooled and cut to obtain pellets. The obtained pellets were fed into a single-screw extruder with a screw diameter of 50 mm and heated to a cylinder temperature of the melting point of the resin (particularly polyamide) + 10°C, and melted to obtain a molten polymer. The molten polymer was filtered using a metal fiber sintered filter (manufactured by Nippon Seisen Co., Ltd., "NF-13", nominal filtration diameter: 60 μm). The molten polymer was then extruded into a film shape from a T-die set to the melting point of the resin (particularly polyamide) + 10°C to obtain a film-like molten material. The molten material was brought into close contact with a cooling roll set to 0°C by electrostatic application and cooled to obtain a substantially unoriented unstretched polyamide film. The resin composition of the polyamide component of the obtained unstretched film was determined, and was found to be substantially the same as the resin composition of the polyamide used.
[0105] The obtained unstretched polyamide film was biaxially stretched by a flat-type simultaneous biaxial stretching machine while holding both ends with clips. The stretching conditions were: preheating section temperature 80°C, stretching section temperature 80°C, MD stretching strain rate 2400% / min, TD stretching strain rate 2400% / min, MD stretching ratio 2.3 times, and TD stretching ratio 2.3 times. After stretching, the film was heat-set at 250°C in the same tenter of the biaxial stretching machine and relaxed by 6% in the width direction to obtain a biaxially stretched polyamide film. The thickness was 100 μm. The resin composition of the polyamide component of the obtained stretched film was determined, and was found to be substantially the same as the resin composition of the polyamide used and the resin composition of the polyamide component of the unstretched film.
[0106] Examples 2 to 20 (Method C; Amino-terminated prepolymer synthesis type two-stage polymerization method, component (C) added all at once) Except for changing the type and amount of monomers charged into the reaction vessel as shown in Table 1 or Table 3, and / or changing the polymerization time in the first polymerization step as shown in Table 1 or Table 3, the same operations as in Example 1 were carried out to obtain pellets, an unstretched film, and a stretched film.
[0107] Comparative Example 1 (Method A: All monomers added at once) A reaction vessel equipped with a heating mechanism, a stirring mechanism, a nitrogen gas inlet, a condensation water outlet, a pressure release port, and a raw material inlet was charged with 37.55 parts by mass of C36 dimer acid (A), 35.57 parts by mass of N36 dimer diamine (B), 12.92 parts by mass of terephthalic acid (C), 13.89 parts by mass of 1,10-decanediamine (D), and 0.19 parts by mass of sodium hypophosphite monohydrate (aqueous solution adjusted to a solid content concentration of 40% by mass) as a catalyst. After that, nitrogen gas with a purity of 99.9999% was purged from the nitrogen gas inlet to replace the inside of the reaction vessel with nitrogen. Next, the reaction vessel was heated to 170°C while stirring under a nitrogen purging atmosphere, and heated for about 2 hours. (At this time, the condensed water generated by the polycondensation reaction in the system became water vapor and was discharged outside the system, so the temperature of the condensed water outlet showed 100-110°C.) After that, the polymerization reaction in the reaction vessel subsided, and the temperature of the condensed water outlet dropped to 90°C, and the temperature of the reaction vessel was raised to 240°C at a heating rate of 10°C / 10 minutes. Next, the temperature of the reaction vessel was raised to 260°C at a heating rate of 10°C / 10 minutes, and the reaction was carried out for 30 minutes, and then the temperature was raised to 290°C at a heating rate of 10°C / 10 minutes. Then, polymerization was carried out at 290°C for 1 hour. After the polymerization was completed, a molten polymer was discharged, containing a large amount of unreacted terephthalic acid and white granular matter that was thought to be a salt of components (C) and (D). The polymer was discharged in a strand, cooled, cut, and dried to obtain polyamide pellets. The melt viscosity of the obtained polyamide was low and it was not possible to form a film, so it was pressed at the melting point +10°C using a hydraulic press to obtain a pressed film with a thickness of 100 μm.
[0108] Comparative Examples 2 and 3 (Method A: All monomers added at once) Except for changing the amount of monomer charged into the reaction vessel as shown in Table 5, the same operation as in Comparative Example 1 was carried out to obtain pellets and pressed films.
[0109] Comparative Example 4 (Method B: Salt synthesis type two-stage polymerization method) 12.98 parts by mass of terephthalic acid and 0.19 parts by mass of sodium hypophosphite monohydrate were charged into a ribbon blender-type reaction apparatus, and heated to 170° C. while stirring at a rotation speed of 30 rpm under nitrogen sealing. Thereafter, while maintaining the temperature at 170° C. and the rotation speed at 30 rpm, 13.46 parts by mass of 1,10-decanediamine heated to 100° C. was continuously added (continuous liquid injection method) using a liquid injection device over a period of 2.5 hours to obtain a reaction product. Into a reaction vessel equipped with a heating mechanism and a stirring mechanism, 37.74 parts by mass of dimer acid and 35.74 parts by mass of dimer diamine were added. After stirring at 100° C. for 1 hour, the above reaction product was added while stirring. The mixture was then heated to 260° C. with stirring, and polymerization was carried out for 5 hours at 260° C. under normal pressure in a nitrogen stream while removing the condensed water from the system. During the polymerization, the system was in a state of a suspended solution. After the polymerization was completed, the mixture was discharged as a strand, which was cooled, cut, and dried to obtain polyamide pellets. A press film was obtained by carrying out the same operation as in Comparative Example 1, except that the pellets were used.
[0110] Comparative Example 5 (Method B: Salt synthesis type two-stage polymerization method) Except for changing the amount of monomer charged into the reaction vessel as shown in Table 5, the same operation as in Comparative Example 4 was carried out to obtain pellets and pressed films.
[0111] Comparative Example 6 (Method C; Amino-Terminated Prepolymer Synthesis Type Two-Stage Polymerization Method, Component (C) Added All at Once) Except for changing the types and amounts of monomers charged into the reaction vessel as shown in Table 5, the same operation as in Example 1 was carried out to obtain pellets, an unstretched film, and a stretched film.
[0112] Comparative Example 7 A polyamide was obtained by carrying out the procedure of Example 4 described in Patent Document 1. Thereafter, an unstretched film and a stretched film were obtained by carrying out the same procedure as in Example 1, except that the pellets were used.
[0113] Comparative Example 8 (Content of Component (A) is 0: Component (B) and Component (D) do not react in the first polymerization step, and a prepolymer is not formed, so this is not Method C) A reaction vessel equipped with a heating mechanism, a stirring mechanism, a nitrogen gas inlet, a condensation water outlet, a pressure release port, and a raw material inlet was charged with 51.16 parts by mass of component (B) N36 dimer diamine, 17.08 parts by mass of component (D) 1,10-decane diamine, and 0.25 parts by mass of sodium hypophosphite monohydrate (aqueous solution adjusted to a solid content concentration of 40% by mass) as a catalyst. After that, nitrogen gas with a purity of 99.9999% was purged from the nitrogen gas inlet to replace the inside of the reaction vessel with nitrogen. The reaction vessel was then heated to 170° C. with stirring under a nitrogen purged atmosphere for approximately 2 hours. After that, the temperature of the reaction vessel was increased to 240°C at a rate of 10°C / 10 minutes. Immediately after the temperature inside the reaction vessel reached 240°C, 31.66 parts by mass of (C) terephthalic acid was added all at once from the raw material inlet of the reaction vessel and polymerized for 1 hour. (At this time, the temperature of the condensation water outlet was 95 to 120°C.) After the temperature of the condensation water outlet dropped to around 90°C, the temperature of the reaction vessel was increased to 260°C at a rate of 10°C / 10 minutes and reacted for 1 hour, and then increased to 290°C at a rate of 10°C / 10 minutes. Polymerization was then carried out at 290°C for 1 hour. After the polymerization was completed, the polymer was discharged as a strand, cooled, cut, and dried to obtain polyamide pellets. Since the melt viscosity of the obtained polyamide was low and it was impossible to form a film, it was pressed at the melting point +10°C using a hydraulic press to obtain a pressed film with a thickness of 100 μm.
[0114] Comparative Example 9 (Content of component (C) is 0: Nothing is added in the second polymerization step, so it is not method C) A reaction vessel equipped with a heating mechanism, a stirring mechanism, a nitrogen gas inlet, a condensation water outlet, a pressure release port, and a raw material inlet was charged with 61.25 parts by mass of C36 dimer acid (A), 29.01 parts by mass of N36 dimer diamine (B), 9.68 parts by mass of 1,10-decanediamine (D), and 0.14 parts by mass of sodium hypophosphite monohydrate (aqueous solution adjusted to a solid content concentration of 40% by mass) as a catalyst. After that, nitrogen gas with a purity of 99.9999% was purged from the nitrogen gas inlet to replace the inside of the reaction vessel with nitrogen. Next, the reaction vessel was heated to 170°C under a nitrogen purged atmosphere while stirring, and heated for about 2 hours. (At this time, the condensed water generated by the polycondensation reaction in the system became water vapor and was discharged outside the system, so the temperature at the condensed water outlet showed 100-110°C.) After that, the polymerization reaction in the reaction vessel subsided, and the temperature of the condensation water outlet dropped to 90°C, after which the temperature of the reaction vessel was increased to 240°C at a rate of 10°C / 10 minutes. The temperature of the reaction vessel was then increased to 260°C at a rate of 10°C / 10 minutes and reacted for 1 hour, and then increased to 290°C at a rate of 10°C / 10 minutes. Polymerization was then carried out at 290°C for 1 hour. After the polymerization was completed, the polymer was discharged as a strand, cooled, cut, and dried to obtain polyamide pellets. Since the melt viscosity of the obtained polyamide was low and it was impossible to form a film, it was pressed at the melting point +10°C using a hydraulic press to obtain a pressed film with a thickness of 100 μm.
[0115] Comparative Example 10 (Content of Component (D) is 0: Method C) A reaction vessel equipped with a heating mechanism, a stirring mechanism, a nitrogen gas inlet, a condensation water outlet, a pressure release port, and a raw material inlet was charged with 30.99 parts by mass of C36 dimer acid (A) and 59.87 parts by mass of N36 dimer diamine (B) and 0.14 parts by mass of sodium hypophosphite monohydrate (aqueous solution adjusted to a solid content concentration of 40% by mass) as a catalyst. After that, nitrogen gas with a purity of 99.9999% was purged from the nitrogen gas inlet to replace the inside of the reaction vessel with nitrogen. Next, the reaction vessel was heated to 170°C under a nitrogen purged atmosphere while stirring, and heated for about 2 hours. (At this time, the condensed water generated by the polycondensation reaction in the system became water vapor and was discharged outside the system, so the temperature at the condensed water outlet showed 100-110°C.) After that, the polymerization reaction in the reaction vessel subsided, and the temperature of the condensed water outlet dropped to 90°C, and then the temperature of the reaction vessel was raised to 240°C at a heating rate of 10°C / 10 minutes. Immediately after the temperature inside the reaction vessel reached 240°C, 9.08 parts by mass of (C) terephthalic acid was added all at once from the raw material inlet of the reaction vessel and polymerized for 1 hour. (At this time, the temperature of the condensed water outlet showed 95 to 120°C.) After the temperature of the condensed water outlet dropped to around 90°C, the temperature of the reaction vessel was raised to 260°C at a heating rate of 10°C / 10 minutes, and the reaction was carried out for 1 hour, and then the temperature was raised to 290°C at a heating rate of 10°C / 10 minutes. Then, polymerization was carried out at 290°C for 1 hour. After the polymerization was completed, the polymer was discharged as a strand, cooled, cut, and dried to obtain polyamide pellets. Since the melt viscosity of the obtained polyamide was low and it was impossible to form a film, it was pressed at the melting point +10°C using a hydraulic press to obtain a pressed film with a thickness of 100 μm.
[0116] Reference example (existing product) The polyamide 12 pellets were dried.
[0117] Tables 1 to 6 show the property values of the polyamides obtained in Examples 1 to 20, Comparative Examples 1 to 10, and Reference Example.
[0118] [Table 1]
[0119] [Table 2]
[0120] [Table 3]
[0121] [Table 4]
[0122] [Table 5]
[0123] [Table 6]
[0124] The polyamides of Examples 1 to 20 were prepared by reacting an aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms with an aliphatic diamine (B) having 18 to 48 carbon atoms and / or an aliphatic diamine (D) having 4 to 16 carbon atoms, and then further adding and reacting an aromatic or aliphatic dicarboxylic acid (C) having 4 to 12 carbon atoms to polymerize the resulting mixture. As a result, all of the Examples had a melting point of 200°C or higher, high heat resistance, a melt viscosity of 40 to 200 Pa·s, excellent moldability, a flexural modulus of 600 MPa or less, high flexibility, and excellent appearance. Comparing Example 3 and Example 20, Example 20 had more amide bonds per carbon atom, and the intermolecular interactions were stronger due to hydrogen bonds, so the flexural modulus was higher.
[0125] In the polyamides of Comparative Examples 1 and 2, components (A) to (D) were added all at once and reacted, so that the melt viscosity measured by a flow tester was less than 40 Pa s, the moldability was poor, and it was not possible to prepare test pieces for measuring the flexural modulus. Furthermore, the haze of the film exceeded 60%, and the appearance was poor.
[0126] The polyamide of Comparative Example 3 was prepared by adding an aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms, an aromatic dicarboxylic acid (C) having 4 to 12 carbon atoms, and an aliphatic diamine (D) having 4 to 16 carbon atoms all at once, and polymerizing them by reaction. As a result, a large amount of unreacted terephthalic acid and salts of components (C) and (D) remained, which became unmelted components and could not be measured by a flow tester. Moreover, because the reaction was insufficient, the melt viscosity was 40 Pa·s or less, and the moldability was poor. Furthermore, the pellets contained particulate matter, and the haze of the film exceeded 60%, resulting in poor appearance.
[0127] The polyamides of Comparative Examples 4 and 5 were prepared by reacting an aromatic dicarboxylic acid (C) having 4 to 12 carbon atoms with an aliphatic diamine (D) having 4 to 16 carbon atoms to produce a reaction product, and then reacting an aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms with an aliphatic diamine (B) having 18 to 48 carbon atoms, and adding the reaction composition to the reaction mixture to carry out polymerization. As a result, the melt viscosity was low. Furthermore, the haze of the film exceeded 60%, and the appearance was poor.
[0128] The polyamide of Comparative Example 6 was prepared by reacting an aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms with an aliphatic diamine (B) having 18 to 48 carbon atoms and an aliphatic diamine (D) having 4 to 16 carbon atoms, and then further adding an aliphatic dicarboxylic acid (C) having 4 to 12 carbon atoms, reacting and polymerizing the resulting mixture, but the melt viscosity was low and the proportion of components (C) + (D) was higher than in Example 20, resulting in a high flexural modulus. Furthermore, the haze of the film exceeded 60%, resulting in poor appearance.
[0129] The polyamide of Comparative Example 7 was polymerized by the method of Example 4 described in Patent Document 1, but had a low melt viscosity and a high flexural modulus because the ratio of components (C)+(D) was higher than that of Example 20. Furthermore, the haze of the film exceeded 60%, resulting in poor appearance.
[0130] The polyamide of Comparative Example 8 was polymerized without adding the aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms, and therefore had a low melt viscosity.
[0131] The polyamide of Comparative Example 9 had a low melt viscosity because it was polymerized without adding an aromatic dicarboxylic acid (C) having 4 to 12 carbon atoms. Furthermore, the heat resistance was also poor.
[0132] The polyamide of Comparative Example 10 was polymerized without adding the aliphatic diamine (D) having 4 to 16 carbon atoms, and therefore had low melt viscosity and poor heat resistance. Furthermore, the haze of the film exceeded 60%, resulting in poor appearance.
[0133] The polyamide of the reference example (existing product) was excellent in moldability, flexibility and appearance, but had a melting point of 172°C and was poor in heat resistance.
[0134] The polyamides of Examples 5, 8, 10, and 12 were produced by carrying out the second polymerization step after the reaction rate of the raw material monomers in the first polymerization step was 20% or more, and therefore all of the examples had excellent molecular weight uniformity and high molecular weight properties. [Industrial Applicability]
[0135] The polyamide and polyamide film of the present invention are useful as packaging materials (eg, packaging materials for medicines; packaging materials for foods such as retort foods; packaging materials for electronic parts such as semiconductor packages).
Claims
1. A unit consisting of an aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms; Units consisting of an aliphatic diamine (B) having 18 to 48 carbon atoms and / or units consisting of an aliphatic diamine (D) having 4 to 16 carbon atoms; and Units consisting of aromatic / aliphatic dicarboxylic acids (C) having 4 to 12 carbon atoms A polyamide comprising: The polyamide has a melt viscosity of 40 to 200 Pa·s.
2. 2. The polyamide according to claim 1, wherein the content of units composed of the aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms is 30 to 80 mass%, the content of units composed of the aliphatic diamine (B) having 18 to 48 carbon atoms is 0 to 45 mass%, the content of units composed of the aromatic / aliphatic dicarboxylic acid (C) having 4 to 12 carbon atoms is 5 to 25 mass%, and the content of units composed of the aliphatic diamine (D) having 4 to 16 carbon atoms is 10 to 40 mass%, based on all monomer components constituting the polyamide.
3. 2. The polyamide according to claim 1, wherein the aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms is a dimer acid.
4. 2. The polyamide according to claim 1, wherein the aliphatic diamine (B) having 18 to 48 carbon atoms is a dimer diamine.
5. 2. The polyamide according to claim 1, wherein the aromatic / aliphatic dicarboxylic acid (C) having 4 to 12 carbon atoms is terephthalic acid.
6. 2. The polyamide according to claim 1, wherein the aliphatic diamine (D) having 4 to 16 carbon atoms is 1,10-decanediamine.
7. 2. The polyamide of claim 1, wherein the polyamide has a melting point of 290° C. or higher.
8. 2. The polyamide of claim 1, wherein the polyamide has a flexural modulus of less than or equal to 600 MPa.
9. 2. The polyamide of claim 1, wherein the polyamide has a haze of 60% or less.
10. 2. The polyamide according to claim 1, wherein the content of the plasticizer component is 0.5 mass % or less based on the polyamide.
11. The polyamide according to claim 1, wherein a ratio (mass ratio) of a total content of the aromatic / aliphatic dicarboxylic acid (C) and the aliphatic diamine (D) to a total content of the aliphatic dicarboxylic acid (A), the aliphatic diamine (B), the aromatic / aliphatic dicarboxylic acid (C), and the aliphatic diamine (D) is 0.10 to 0.
60.
12. The polyamide according to claim 1, wherein the value of the following formula (1) is 0.30 or less. (MnMax-MnMin) / MnMax (1) (MnMax and MnMin respectively indicate the maximum and minimum values of the number average molecular weight.)
13. a first polymerization step of reacting an aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms with an aliphatic diamine (B) having 18 to 48 carbon atoms and / or an aliphatic diamine (D) having 4 to 16 carbon atoms; and After the first polymerization step, an aromatic / aliphatic dicarboxylic acid (C) having 4 to 12 carbon atoms is further added and reacted in a second polymerization step. A method for producing a polyamide, comprising: a ratio (mass ratio) of a total amount of the aromatic / aliphatic dicarboxylic acid (C) and the aliphatic diamine (D) used to a total amount of the aliphatic dicarboxylic acid (A), the aliphatic diamine (B), the aromatic / aliphatic dicarboxylic acid (C), and the aliphatic diamine (D) used is 0.10 to 0.
60.
14. After the first polymerization step, the unreacted terminal groups of the aliphatic dicarboxylic acid (A) having 18 to 48 carbon atoms are 1 The relationship between the peak integrals of the H-NMR spectrum and the amine end groups of the reactants and the starting monomers. 1 The method for producing a polyamide according to claim 13, wherein the ratio of peak integral values in a H-NMR spectrum is 20% or more.
15. A method for producing the polyamide according to claim 13, which comprises producing the polyamide according to any one of claims 1 to 12.
16. A film comprising the polyamide according to any one of claims 1 to 12.
Citation Information
Patent Citations
Polyamide containing monomer units of 1,4-butylenediamine
JP2014506614A
Flexible polyamide
WO2020085360A1
Polyamide, molded body and film formed of same, and method for producing said polyamide
WO2022054944A1